DISINFORMATION AND DIGITAL ELECTORAL CRIMES: CHALLENGES FOR DEMOCRACY (CIPEEX, 2025)
The 2024 municipal elections in Brazil demonstrated that the advancement of digital technologies directly impacts the functioning of democracy, particularly in the dissemination of false information. This study analyzes how technological resources especially those capable of producing manipulated content with a realistic appearance were used both to influence the electoral debate and to counter it. The objective was to understand how these technologies affect the integrity of elections and to identify the strategies adopted to mitigate their harmful effects. The research employed a qualitative approach, based on the review of laws, legislative proposals, and data published by the Superior Electoral Court (TSE) and regional electoral courts, in addition to the analysis of incidents from the 2022 and 2024 elections. The results indicate that the TSE adopted measures requiring the identification of content produced through advanced technological means and prohibited the dissemination of false materials intended to manipulate the electoral process, establishing severe penalties. Regional initiatives, such as the creation of systems to detect altered audio by the Regional Electoral Court of Paraíba (TRE-PB) in partnership with the Federal University of Paraíba (UFPB), showed potential in combating disinformation. Nevertheless, the rapid evolution of these tools outpaces regulatory and oversight capacity, making it difficult to identify those responsible and to ensure effective action from digital platforms. It is concluded that combating electoral disinformation in Brazil requires constant updating of regulations, strengthening of oversight mechanisms, development of new technological solutions, and active participation from civil society to ensure free and transparent elections.